President Trump vs. CEOs: a comparison of presidential and corporate agenda building. Issue 1 (3rd March 2020) - Lan, Xiaomeng; Tarasevich, Sofiya; Proverbs, Pamala; Myslik, Barbara; Kiousis, Spiro
ABSTRACT: The purpose of this study was to compare the agenda-building influence of President Trump and CEOs in communicating about a number of political and social issues. Through a content analysis of the president's (N = 63) and business leaders' (N = 234) information subsidies and news coverage (N = 270), evidence was found repeatedly supporting the president's first, second, and third levels of agenda-building influence on news media content. In comparison, CEOs' agenda-building influence was found at the first and third levels, and this influence was not consistent across issues. Furthermore, an argument was made in light of the study's findings that direct communication by business leaders generally had a more significant impact on the media agenda than indirect messages from other organizational actors such as their companies or corporate spokespeople.